Lignans and terpenoids from the stem of Ephedra equisetina Bunge. (August 2022) - Zhu, Deng-Hui; Zhang, Jing-Ke; Jia, Ju-Fang; Liu, Juan-Juan; Wei, Jun-Jun; Yang, Meng; Yang, Ying; Li, Meng; Hao, Zhi-You; Zheng, Xiao-Ke; Feng, Wei-Sheng
Abstract: Seven undescribed lignans, equiselignan A–F, and six undescribed terpenoids, equiseterpenoid A–E (including two pairs of enantiomers, (+/−)-equiselignan A and (+/−)-equiseterpenoid E), were isolated from the stems of Ephedra equisetina Bunge. Their structures were elucidated by spectroscopic methods, and the absolute configurations of the undescribed compounds were determined by interpretation of their electronic circular dichroic (ECD) and optical rotation data. In β -hexosaminidase ( β -Hex) release assay, anti-asthmatic activities of all of the compounds were evaluated by releasing β -Hex in C48/80-induced RBL-2H3 cells. The β -Hex release rates of equiselignan B and equiseterpenoid B were 0.86 ± 0.094 and 0.86 ± 0.012 by comparing with model group, whereupon equiselignan B and equiseterpenoid B exhibited significant anti-asthmatic activities. Graphical abstract: Image 1 Highlights: Thirteen undescribed compounds were isolated from the stems of E. equisetina. Their structures were elucidated by NMR and mass spectrometry. The absolute configurations were deduced by interpretation of ECD and [α] data. The anti-asthmatic activities of all the isolated compounds were evaluated.